Lipocalin-2 promotes breast cancer brain metastasis by enhancing tumor invasion and modulating brain microenvironment - Zhao, Yang; Tang, Xiaogen; Lei, Tingting; Fu, Dongwei; Zhang, Hongyi (Frontiers in Oncology, 2024)
Breast cancer is the leading cancer diagnosed in women globally, with brain metastasis emerging as a major cause of death, particularly in human epidermal growth factor receptor 2 positive and triplenegative breast cancer subtypes. Comprehensive understanding of the molecular foundations of central nervous system metastases is imperative for the evolution of efficacious treatment strategies. Lipocalin-2 (LCN2), a secreted iron transport protein with multiple functions, has been linked to the progression of breast cancer brain metastasis (BCBM). In primary tumors, LCN2 promotes the proliferation and angiogenesis of breast cancer cells, triggers the epithelial-mesenchymal transition, interacts with matrix metalloproteinase-9, thereby facilitating the reorganization of the extracellular matrix and enhancing cancer cell invasion and migration. In brain microenvironment, LCN2 undermines the blood-brain barrier and facilitates tumor seeding in the brain by modulating the behavior of key cellular components. In summary, this review meticulously examines the fuel role of LCN2 in BCBM cascade, and investigates the potential mechanisms involved. It highlights the potential of LCN2 as both a therapeutic target and biomarker, indicating that interventions targeting LCN2 may offer improved outcomes for patients afflicted with BCBM.